Uptake of Immediate Postpartum LARCs and Associated Factors among Mothers Who Gave Birth at Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia - Tariku, Mequanent; Legesse, Biruk; Tantu, Temesgen; Duko, Bereket (International Journal of Reproductive Medicine, 2022)
Background. Postpartum family planning is an effective strategy for reducing maternal and childhood morbidity and mortality by preventing unintended pregnancy and short interpregnancy intervals. Despite the paramount advantages of long-acting reversible contraceptives (LARC), their uptake remains low in Ethiopia. Therefore, the aim of this study was to assess the uptake of immediate postpartum LARC methods and its associated factors among women who gave birth in Hawassa University Comprehensive Specialized Hospital, Hawassa city, Southern Ethiopia. Methods. An institution-based cross-sectional study was conducted among 418 eligible mothers who were in the immediate postpartum period. Data were collected using a pretested structured questionnaire before their discharge from the hospital and analyzed by using SPSS version 20. The statistical significance was declared at P value less than 0.05. Results. The uptake LARCs among immediate postpartum mothers was 25.4%. The most commonly reported reasons for not using LARC were preference to start contraception after six weeks of delivery (43.3%) and the need to use other methods of contraception (26%). Having unplanned birth (AOR: 1.97; 95% CI: 1.04-3.71) and receiving family planning counselling on LARCs during the postpartum period (AOR: 21.1; 95% CI: 6.49-68.66) were factors significantly associated with immediate postpartum LARC use. Conclusion. Low utilization of immediate postpartum LARC uptake was found in the current study setting. There was increased utilization of immediate postpartum LARC among mothers who received family planning counselling during the postpartum period. Therefore, strengthening family planning counselling during the immediate postpartum period is crucial to enhance postpartum LARC use.